Milan Kundera and His Novel “The Unbearable Lightness of Being” - Dadyan, Kristine (Bulletin of Yerevan University B: Philology, 2025)
The aim of the study is to analyze the abstract concepts of the lightness and heaviness of existence in Milan Kundera’s philosophical novel The Unbearable Lightness of Being through its characters. The main characters — Dr. Tomas, his wife Teresa, his mistress Sabina, and Sabina’s lover Franz — represent different approaches to these concepts. In the novel, lightness and heaviness constantly intertwine, creating internal conflicts and suffering. The characters in Kundera’s novel live in a world where the lightness and heaviness of existence, as opposing forces, penetrate every action and choice they make. These forces become not only the philosophical backdrop of the work but also determining factors in the lives of the characters. The study aims to reveal the connection between the lightness and heaviness of existence as philosophical categories, and how they influence human freedom and fate. The relevance of the study is determined by the growing interest in existential questions in literature, as well as the exploration of philosophical concepts within the context of literary works.